2006
DOI: 10.1128/jvi.00936-06
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Genetic Recombination Is a Common Feature of Primate Lentivirus Replication

Abstract: Recent studies indicate that human immunodeficiency virus type 1 (HIV-1) recombines at exceedingly high rates, approximately 1 order of magnitude more frequently than simple gammaretroviruses such as murine leukemia virus and spleen necrosis virus. We hypothesize that this high frequency of genetic recombination is a common feature of primate lentiviruses. Alternatively, it is possible that HIV-1 is unique among primate lentiviruses in possessing high recombination rates. Among other primate lentiviruses, only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 64 publications
(68 reference statements)
0
33
0
1
Order By: Relevance
“…For both HIV-1 and gammaretroviruses, reducing RNase H activity decreased template switching (37,234). These findings suggested that retroviruses with low RNase H activity, such as HIV-2 (132), would recombine less frequently than HIV-1, which possesses robust RNase H. However, subsequent studies demonstrated that rates of template switching are very similar for HIV-2 and HIV-1 (50,221).…”
Section: Enzymology Of Recombinationmentioning
confidence: 58%
See 2 more Smart Citations
“…For both HIV-1 and gammaretroviruses, reducing RNase H activity decreased template switching (37,234). These findings suggested that retroviruses with low RNase H activity, such as HIV-2 (132), would recombine less frequently than HIV-1, which possesses robust RNase H. However, subsequent studies demonstrated that rates of template switching are very similar for HIV-2 and HIV-1 (50,221).…”
Section: Enzymology Of Recombinationmentioning
confidence: 58%
“…The current consensus from experimental studies is that HIV-1 recombinogenic template switching occurs at the remarkable rate of roughly every 2 kb or possibly even more frequently under some physiological conditions (11,50,275). This section introduces the approaches that led to these conclusions and the properties of virus replication that are responsible.…”
Section: Frequency and Mechanism Of Hiv-1 Genetic Recombinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies to date have measured recombination rates in a number of elegant ways. The use of retroviral reporter systems, where correctly positioned recombination will recreate a functional foreign gene insert conferring antibiotic resistance or fluorescence (16)(17)(18), allows for the rapid screening of recombinants but does not allow the measurement of recombination on the natural HIV-1 sequence. A more direct method of detecting recombination is through the sequenc-ing of reverse transcription products derived from an authentic HIV-1 replication cycle.…”
mentioning
confidence: 99%
“…Others have taken advantage of retroviral vector or reporter systems, in which the expressions of reporter genes (such as fluorescent proteins, cell surface markers, and/or antibiotic resistance genes) were used to select cells containing recombined viral genomes for recombination and mutation analyses (28)(29)(30)(31)(35)(36)(37)(38)(39). As coexpression of reporter gene products in a single cell is needed to identify recombination events, these systems generally use a low multiplicity of infection (MOI) to avoid dual infection introducing experimental bias (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). However, as these systems require expression of the gene products, natural mutation events or recombination events that lead to nonproductive expression of reporter genes will be unaccounted for.…”
mentioning
confidence: 99%